2019
DOI: 10.1016/j.chemgeo.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption spectroscopic investigation of the Ca and Mg environments in CO2-bearing silicate glasses

Abstract: Recent investigation showed that the CO 2 solubility in silicate melts is strongly affected by the #Mg (MgO/MgO+CaO). CO 2 solubility is decreasing with increasing #Mg implying that CO 2 molecules dissolves in the vicinity of Ca atoms to form CO 3 2molecular groups. We have investigated several CO 2-bearing (up to 17.2 wt.%) silicate glasses using X-ray Absorption Spectroscopy (XAS) at the Mg and Ca K-edge in order to determine the structural environments of Mg 2+ and Ca 2+ cations. Analyses of the Mg XANES re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Prior to the simulation, the EXAFS spectra were calibrated for the scattering amplitude and corrected for the edge position [56]. We simulated the spectrum obtained on CaI 2 with the CaI 2 crystalline model.…”
Section: L 3 -Edge Exafsmentioning
confidence: 99%
“…Prior to the simulation, the EXAFS spectra were calibrated for the scattering amplitude and corrected for the edge position [56]. We simulated the spectrum obtained on CaI 2 with the CaI 2 crystalline model.…”
Section: L 3 -Edge Exafsmentioning
confidence: 99%
“…The XANES spectrum of the slag core was composed of four main features, located at about 1306.1 eV for a pre-edge peak P, 1309.2 eV and 1314.2 eV for two main features A and B, and 1326.0 eV for a broader peak C. Previous studies on Mg-bearing minerals and silicate glasses have attributed these features to various Mg environments. [51][52][53][54][55] The pre-edge peak P was assigned to a highly asymmetric environment of the first coordination shell. Peak A was related to the coordination number of Mg, as its position shifts towards higher energies when the coordination number increases from [4] Mg (1307.2 eV) to [8] Mg (1309.7 eV) in various Mg-bearing minerals.…”
Section: Mg K-edge Xanes Measurementsmentioning
confidence: 99%
“…One hypothesis for explaining the absence of S effect on CO2 solubility is that CO2 and S have two distinct dissolution mechanisms with different surrounding cations. Recent work (Morizet et al 2019) showed that CO3 2groups in depolymerized glasses are mostly dissolved in the surrounding of Ca 2+ cations (and not Mg 2+ ). Currently, the cationic affinity for SO4 2groups is unknown.…”
Section: So2 and Co2 Dissolution Mechanisms And Implication For Volatile Transport By Kimberlitic Meltmentioning
confidence: 99%